Parameter differentiation method in solution of axisymmetric soft shells stationary dynamics nonlinear problems - Ekaterina A. Korovaytseva (Vestnik Samarskogo Gosudarstvennogo Tehničeskogo Universiteta. Seriâ: Fiziko-Matematičeskie Nauki, 2021)
An algorithm of axisymmetric unbranched soft shells nonlinear dynamic behaviour problems solution is suggested in the work. The algorithm does not impose any restrictions on deformations or displacements range, material properties, conditions of fixing or meridian form of the structure. Mathematical statement of the problem is given in vector-matrix form and includes system of partial differential equations, system of additional algebraic equations, structure segments coupling conditions, initial and boundary conditions. Partial differential equations of motion are reduced to nonlinear ordinary differential equations using method of lines. Obtained equation system is differentiated by calendar parameter. As a result problem solution is reduced to solving two interconnected problems: quasilinear multipoint boundary problem and nonlinear Cauchy problem with right-hand side of a special form. Features of represented algorithm using in application to the problems of soft shells dynamics are revealed at its program realization and are described in the work. Three- and four-point finite difference schemes are used for acceleration approximation. Algorithm testing is carried out for the example of hinged hemisphere of neo-hookean material dynamic inflation. Influence of time step and acceleration approximation scheme choice on solution results is investigated.